Effects of nanozyme on environmental fate and dissemination of antibiotic resistance genes in anaerobically digested sludge - Jing Wang; Peng Li; Ningyu Gao; Jun Ma; Defeng Xing (Bioresource Technology, 2026)

Rare Bacterial Taxa Drive Soil Multifunctionality in Lakeside Wetlands of Eutrophic Lake - Lingchen Yuan; Jiajia Zhang; Mengxi Gao; Renlei Yang; Yue Chen; Bin Hu; Defeng Feng; Wei Li (Wetlands, 2026)

Elastic conductive polyurethane/PEDOT:PSS composite with self-healing and closed-loop recyclability - Wei-Chen Gao; Ben Fan; Junmei Hu; Yu-Dong Zhao; Xiang Sun; Defeng Cui; Jing Qiao; Wei-Bing Lu; Ying-Shi Guan (Chemical Engineering Journal, 2025)

Landslide susceptibility assessment using AutoML-SHAP method in the southern foothills of Changbai Mountain, China - Defeng Zheng; Yuanyuan Li; Chenglin Yan; Hao Wu; Yosuke Alexandre Yamashiki; Botong Gao; Tingkai Nian (Landslides, 2025)

Development of CadR-based cadmium whole cell biosensor for visual detection of environmental Cd2+ - Tianyi Zhang; KaiLi Zhu; Xia Zhang; Xin Yu; Liang Shen; Defeng Gao; Yiwen Chen; Qinghua Wang; Shaopeng Chen; Lingzhi Bao (Analytica Chimica Acta, 2024)

Integrating network pharmacology and experimental validation to explore the mechanisms of luteolin in alleviating fumonisin B1–induced intestinal inflammatory injury - Defeng Wen; Wantong Han; Quan Chen; Guanhui Qi; Mengling Gao; Pu Guo; Yu Liu; Zhongyuan Wu; Shulin Fu; Qirong Lu; Yinsheng Qiu (Toxicon, 2024)

Pathogenicity of duck circovirus and fowl adenovirus serotype 4 co-infection in Cherry Valley ducks - Mingyue Shen; Panpan Gao; Cheng Wang; Ning Li; Shuyu Zhang; Yunxuan Jiang; Defeng Liu; Baoyu Jia; Li Xu; Bohan Huang; Ruiliang Zhu; Kai Wei (Veterinary Microbiology, 2023)

Comparative Transcriptome Analysis of Spleen Reveals Potential Regulation of Genes and Immune Pathways Following Administration of Aeromonas salmonicida subsp. masoucida Vaccine in Atlantic Salmon (Salmo salar) - Qiang Fu; Yuqing Li; Hao Zhang; Min Cao; Lu Zhang; Chengbin Gao; Xin Cai; Defeng Chen; Ziying Yang; Jie Li; Ning Yang; Chao Li (Marine Biotechnology, 2022)

Capsular polysaccharide of Streptococcus agalactiae is an essential virulence factor for infection in Nile tilapia ( Oreochromis niloticus Linn.) - Defeng Zhang; Xiaoli Ke; Zhigang Liu; Jianmeng Cao; Youlu Su; Maixin Lu; Fengying Gao; Miao Wang; Mengmeng Yi; Fengling Qin (Journal of Fish Diseases, 2019)
Streptococcus agalactiae (Group B Streptococcus , GBS) is associated with diverse diseases in aquatic animals. The capsule polysaccharide (CPS) encoded by the cps gene cluster is the major virulence factor of S. agalactiae ; however, limited information is available regarding the pathogenic role of the CPS of serotype Ia piscine GBS strains in fish. Here, a non‐encapsulated mutant (Δ cps ) was constructed by insertional mutagenesis of the cps gene cluster. Mutant pathogenicity was evaluated in vitro based on the killing of whole blood from tilapia, in vivo infections, measuring mutant survival in tilapia spleen tissues and pathological analysis. Compared to wild‐type (WT) GBS strain, the Δ cps mutant had lower resistance to fresh tilapia whole blood in vitro ( p 0.01), and more easily cleared in tilapia spleen tissue, and was highly attenuated in tilapia and zebrafish. Additionally, compared to the Δ cps mutant, numerous GBS strains and severe tissue necrosis were observed in the tilapia spleen tissue infected with WT strains. These results indicated that the CPS is essential for GBS pathogenicity and may serve as a target for attenuation in vaccine development. Gaining a better understanding of the role, the GBS pathogenicity in fish will provide insight into related pathogenesis and host–pathogen interactions.

Spatial-temporal dynamics of soil chloride distribution in a coastal saline plain: implication for ocean and climate influences - Shaofeng Yan; Lu Zhai; Qiuliang Deng; Defeng Pan; Shikai Gao; Chaowang Zou (Journal of Soils and Sediments, 2018)